2014
DOI: 10.3109/02713683.2014.957776
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofl-Carnitine, Erythritol and Betaine on Pro-inflammatory Markers in Primary Human Corneal Epithelial Cells Exposed to Hyperosmotic Stress

Abstract: Purpose To explore the effects of osmoprotectants on pro-inflammatory mediator production in primary human corneal epithelial cells (HCECs) exposed to hyperosmotic stress. Methods HCECs cultured in iso-osmolar medium (312mOsM) were switched to hyperosmotic media with or without prior incubation with 2–20mM of L-carnitine, erythritol or betaine for different time periods. The mRNA expression and protein production of pro-inflammatory markers in HCECs were evaluated by RT-qPCR and ELISA. Results Hyperosmolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 56 publications
(64 reference statements)
2
55
0
1
Order By: Relevance
“…Further studies could explore patient preference while rheological studies could evaluate viscosity under shear stress in gel-based formulations to determine which components provide optimal performance in terms of symptom improvement and tolerability. A number of osmoprotectants, including L-carnitine and erythritol, have already shown a potential anti-inflammatory effect in corneal epithelial cells under osmotic stress [36]. Additional studies that include measures of markers of cellular stress could help elucidate effects of the additional components in the CMC-GLY formulation.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies could explore patient preference while rheological studies could evaluate viscosity under shear stress in gel-based formulations to determine which components provide optimal performance in terms of symptom improvement and tolerability. A number of osmoprotectants, including L-carnitine and erythritol, have already shown a potential anti-inflammatory effect in corneal epithelial cells under osmotic stress [36]. Additional studies that include measures of markers of cellular stress could help elucidate effects of the additional components in the CMC-GLY formulation.…”
Section: Discussionmentioning
confidence: 99%
“…L-carnitine as an organic osmoprotectant 19,20 has been proven to have protective roles against production of proinflammatory mediators 21 and apoptosis 16 in primary HCECs exposed to hyperosmotic media, as well as in dry-eye patients 36,37 and animal models. 15 However, the antioxidative effects of Lcarnitine are not well understood in an in vitro dry-eye model.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] Recently, osmoprotectants, L-carnitine, erythritol, and betaine, have been demonstrated to inhibit in HCECs and in a dry-eye mouse model hyperosmotic-induced increases in proinflammatory cytokines (TNF-a, IL-1b, IL-6, and IL-17) and chemokines (IL-8, CCL2, and CCL20). 15,21 We further showed their suppressive effects on the expression, production, and activity of matrix metalloproteinases (MMP-13, MMP-2, MMP-9, MMP-3, and MMP-7) induced by hyperosmotic media in primary HCECs. 22 We also observed that L-carnitine and erythritol protected HCECs from hyperosmotic stress via suppressive effect on activation of c-Jun N-terminal kinases (JNK) and p38MAP kinase.…”
mentioning
confidence: 88%
“…Osmoprotectants such as L-carnitine, erithritol, or betaine have been shown to significantly reduce HO-induced proinflammatory responses, 15 to promote the survival of corneal epithelial cells, and protect the integrity of the epithelium. [16][17][18] We therefore tested the effects of these molecules on wound healing under HO conditions ( Figure 5).…”
Section: Effects Of Osmoprotectants On Ho Cytotoxicity and Rgtasmentioning
confidence: 99%